Nursing of a patient with incomplete bowel obstruction treated by intradermal acupuncture combined with auricular acupoint pressing therapy (皮内针联合耳穴压豆改善1例不完全性肠梗阻患者症状的护理体会) - LIANG Ying (梁颖); ZHAO Junying (赵俊英) (Association of Integrative Nursing, 2023)
This article summarized the nursing of a patient with incomplete bowel obstruction treated by intradermal acupuncture combined with auricular acupoint pressing therapy. The patient received a comprehensive evaluation and risk assessment after hospital admission. In addition to routine nursing interventions such as pain control, prevention of complications and psychological care, intradermal acupuncture combined with auricular acupoint pressing guided by the holistic view of Traditional Chinese Medicine was carried out to improve the recovery of bowel movement and relieve the bowel obstruction and related discomfort. (本文总结采用皮内针联合耳穴压豆改善1例不完全性肠梗阻患者症状的护理经验。患者入院后积极完善检查和评估, 结合辨证分型, 在疼痛干预、预防并发症、心理护理等常规护理基础上, 基于中医整体观, 采用皮内针联合耳穴压豆干预, 疏通脏腑、促进肠蠕动、顺气导滞, 帮助患者快速安全地解除梗阻状态, 改善不适症状。)